2009
DOI: 10.1016/j.jadohealth.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Like Parent, Like Child: Intergenerational Transmission of Partner Violence in Cebu, the Philippines

Abstract: Purpose This study investigates the prevalence of partner violence perpetration and receipt among a sample of young men and women in the Philippines, as well as the relationship between witnessing inter-parental violence during childhood and current violence in partnerships. Methods We used 1994, 2002, and 2005 data from 472 married or cohabiting young adults from the Cebu Longitudinal Health and Nutrition Survey in Cebu, Philippines. This is a longitudinal data set following over 2,000 Filipino women and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 38 publications
7
64
1
9
Order By: Relevance
“…This finding is consistent with the scant research that has examined both IPV victimization and perpetration by women in low-income countries [3,25,[27][28][29][30][31] and may partially be because of overall underreporting of male IPV perpetration. Males may be more likely to underreport violence perpetration in surveys because of the unacceptability of the behavior, and underreport victimization because of embarrassment or not conceptualizing acts as violent.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is consistent with the scant research that has examined both IPV victimization and perpetration by women in low-income countries [3,25,[27][28][29][30][31] and may partially be because of overall underreporting of male IPV perpetration. Males may be more likely to underreport violence perpetration in surveys because of the unacceptability of the behavior, and underreport victimization because of embarrassment or not conceptualizing acts as violent.…”
Section: Discussionsupporting
confidence: 88%
“…Scaling up these programs to reach youth in schools may be worthwhile in Brazil and globally. Future research in this area will inform interventions to address the complex interplay of factors that underlies 31.0 (13) Victim filed complaint with police 12.5 (8) .0 (0) Victim left partner 9.4 (6) 4.8 (2) Victim talked with perpetrator 6.4 (4) .0 (0) Victim stayed in a shelter 3.1 (2) 2.4 (1) Victim responded emotionally (cried, shouted, was upset, angry, etc. )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation of the present study was at par with these studies. Several studies have shown that women who were more highly educated (secondary schooling or higher) were 20-55% less likely to be victims of intimate partner violence or sexual violence compared to less-educated women (17,27,28). In the present study, most of the study population; 60.3 %, had never married.…”
Section: Discussionmentioning
confidence: 44%
“…Children who grew up in Both violent households were five times more likely to assault a partner than those from Male-only DCT households (Fehringer & Hindin, 2008).…”
Section: Intergenerational Transmission Of Partner Violencementioning
confidence: 91%